The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2136/sssaj2018.01.0036
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of In‐Season Soil Nitrogen Tests for Corn Planted into Winter Annual Cover Crops

Abstract: Core Ideas The Solvita 1‐d CO2 mineralization test could be a new tool to improve in‐season N rate recommendations for corn. Solvita and soil NO3–N tests may be useful for predicting the level of early‐season N mineralization from winter cover crops (WCCs). Soil NO3–N collected at the V4 growth stage of corn at 0 to 15 cm was positively correlated (R2 = 0.45) with corn check yield. Neither the Solvita nor the presidedress nitrate test detected WCC N mineralization consistently enough to use them in rate recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Other studies also reported a lack of strong response of Nmin estimated from HSHT parameters to agromanagement practices (Castro Bustamante & Hartz, 2016; Dick & Culman, 2016; Tu, 2016; Moore, Guillard, Morris, & Brinton, 2019). In addition, some studies discussed the limited applicability of using Nmin in predicting crop N fertilizer requirement due to the requirement of advanced yield estimation, high measurement variability of HSHT indicators, and region‐specific calibration and validation of such predictions (Norris, Chim, Evanylo, Reiter, & Thomason, 2018; Stahl, Fernández, & Kaiser, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also reported a lack of strong response of Nmin estimated from HSHT parameters to agromanagement practices (Castro Bustamante & Hartz, 2016; Dick & Culman, 2016; Tu, 2016; Moore, Guillard, Morris, & Brinton, 2019). In addition, some studies discussed the limited applicability of using Nmin in predicting crop N fertilizer requirement due to the requirement of advanced yield estimation, high measurement variability of HSHT indicators, and region‐specific calibration and validation of such predictions (Norris, Chim, Evanylo, Reiter, & Thomason, 2018; Stahl, Fernández, & Kaiser, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The SSCB test has been reported to distinguish CO 2 respiration differences between various treatment effects in cropped and noncropped situations (Goupil and Nkongolo. 2014; Sadeghpour et al, 2016; Sciarappa et al, 2017; Mureva and Ward, 2017; Ward et al, 2017; Chahal and van Eerd, 2018; Norris et al, 2018). As a predictor of plant growth or crop yield, though, the SSCB test has not been reliable or consistent in the few published peer‐reviewed field studies that used this test (Castro Bustamante and Hartz, 2016; Ward et al, 2017; Chahal and van Eerd, 2018; Bamber et al, 2018; Norris et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As an assessment of soil CO 2 respiration, the SSCB test has been evaluated in various crop and grassland systems (Goupil and Nkongolo, 2014; McDonald et al, 2014; Castro Bustamante and Hartz, 2016; Sadeghpour et al, 2016; Sciarappa et al, 2017; Mureva and Ward, 2017; Ward et al, 2017; Bamber et al, 2018; Chahal and van Eerd, 2018; Norris et al, 2018). The SSCB test is positively and significantly ( P < 0.05) correlated with SOM (McDonald et al, 2014; Castro Bustamante and Hartz, 2016; Sadeghpour et al, 2016; Rogers et al, 2018), soil total organic C and N (Haney et al, 2012; McDonald et al, 2014), soil N mineralization (Haney et al, 2008b; McDonald et al, 2014; Castro Bustamante and Hartz, 2016; Rogers et al, 2018), plant‐mineralizable N (Norris et al, 2018), soil water‐extractable organic C and N (Haney et al, 2012; Castro Bustamante and Hartz, 2016), soil P mineralization (Haney et al, 2008b), and chloroform fumigation extraction microbial biomass C (Chatterjee and Acharya, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, both spot and integrated samples can be analyzed using colorimetric techniques. For spot samples, colorimetric tubes can be used (Patil et al, 2010), while colorimetric paddles can provide integrated flux measurements (Sciarappa et al, 2016;Norris et al, 2018). Micro-respiration measurements, which quantify soil respiration and microbial community physiological profiles using indicator dyes in agar gel, also use colorimetric techniques (Campbell et al, 2003;Renault et al, 2013).…”
Section: Introductionmentioning
confidence: 99%